A new technique for the characterization of long-range tertiary contacts in large RNA molecules: insertion of a photolabel at a selected position in 16S rRNA within the Escherichia coli ribosome. - Baranov, P V (1997)
A new approach for inserting a photo-label at a selected position within the long ribosomal RNA molecules has been developed. The Escherichia coli 16S rRNA was cleaved at a single internucleotide bond, 1141-1142, with RNase H in the presence of a complementary chimeric oligonucleotide. 4-Thiouridine 5', 3'-diphosphate was ligated to the 3'-end of the 5'fragment at the cleavage site with T4 RNA ligase. The 16S rRNA fragments containing this added photo-reactive nucleotide were assembled together with total 30S ribosomal proteins into small ribosomal subunits. The ability of such 30S particles containing fragmented rRNA to form 70S ribosomes has been demonstrated previously. Crosslinks were induced within the 30S subunits by mild UV irradiation. The sites of crosslinking within the 16S rRNA were then analyzed using RNase H digestion and reverse transcription. Two crosslinks from the thio-nucleotide attached to nt C1141 of 16S rRNA were observed, namely to nt U1295 and G1272. These results are in agreement with the established proximity of helix 39 and 41 in the 3D structure of the 30S ribosomal subunit, as shown by other intra RNA crosslinking data. These data furthermore allow us to refine the structural arrangement of helices 41 and 39 relative to one another.